Appending Transgender Equal Rights to Gay, Lesbian and Bisexual Equal Rights - Adler, Libby (Columbia Journal of Gender and Law, 2010)
In recent years, the identity group of transgender persons has been cohering and bringing its concerns to the attention of progressive legal thinkers as well as to organs of government. In the domain of conventional anti-discrimination coverage, the result has been a number of local ordinances, a few state laws and a modest number of victories in judicial settings. In addition, advocates for transgender concerns have taken up family issues such as whether gender identity poses obstacles to child custody, access to medical services associated with gender transition and the processes for legally changing one’s name and gender. The law review literature in this area has taken off like a rocket. Much of the academic thought devoted to transgender issues has focused on the problem of judicial determinations of an individual’s gender, whether and how to gain coverage for gender identity under Title VII, the advantages and pitfalls of a disability-rights framework that medicalizes trans identity, issues specific to youth (especially youth in foster care and in the juvenile justice system), prisoner classification and sex- segregation and insurance coverage for gender-affirming care. A few critically-inclined thinkers have focused on the power that formal and discretionary bureaucratic decisions have on trans people and on the limits of formal equality, though these voices are a bit lonely.